Formas de nitrogênio como atenuadores do estresse salino em plantas de abobrinha - Fernandes, Cleyton dos Santos (Universidade Federal Rural do Semi-Árido, 2019)
Salt stress is one of the most restrictive abiotic factors in plant growth and yield in the world, especially in arid and semi-arid zones. In order to improve the acclimatization of plants to salt stress, several management strategies are studied, especially those with potential to improve the absorption and assimilation of nutrients. In this context, the present research aimed to study the effects of nitrate and ammonium ions on the attenuation of salt stress in zucchini plants (Caserta cv.) grown in a hydroponic system. The experiment was carried out in a greenhouse, in an experimental design of randomized blocks, arranged in a 2 x 5 factorial scheme, with 4 replications. The treatments consisted of two specific forms of nitrogen (nitrate - NO3- and ammonium - NH4+) and five levels of electrical conductivity of the irrigation water (ECw) (0.5, 2.0, 3.5, 5.0 e 6.5 dS m-1). The plants were grown until the production phase in pots with capacity of 8 dm3, filled with coconut fiber-based substrate. The plants were evaluated for growth, gas exchange, chlorophyll a fluorescence, chloroplastidic pigments, percentage of leaf cell damage, aerial shoot composition and yield. The results were analyzed through analysis of variance, with significance being verified at the 5% probability level of the treatments using the F test. The results indicated that the exclusive nutrition with nitrogen in the form of NH4+ promotes reduction in the growth and accumulation of biomass of Italian zucchini plants. These plants present greater restrictions in the photochemical and photosynthetic efficiency than those fed with NO3- when grown under salinity conditions. In addition, they present premature death in the flowering phase, regardless of the saline stress condition. Nitrogen nutrition in the form of NO3- is indicated for the hydroponic cultivation of zucchini. Irrigation with water of electrical conductivity higher than 2.0 dS m-1 reduces growth, gas exchange, photochemical and non-photochemical efficiency, nutrient accumulation in the aerial part of plants and production of Italian zucchini. It is suggested to carry out other similar researches to deepen the knowledge under the possible potential of NO3- and NH4+ ions in the attenuation of salinity effects in zucchini and other cucurbit plants
Keywords: Cucurbita pepo L; Salinidade; Adubação nitrogenada; Cucurbita pepo L; Salinity; Nitrogen fertilization; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO